(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The paper aims at analysing the role of medical professional ethics in the plurality of pluralisms (legal, axiological and material) affecting medical profession, patient healthcare and medical liability. Accordingly, the essay focuses – from a comparative perspective – on the role, the strengths and weaknesses of both the code of medical ethics and the disciplinary procedures in the Italian legal system, trying to stress some of the main intricate issues concerning the multi-faceted interconnec- tions between law and medical ethics, and between state and profession. In these perspectives, the medical professional ethics proves to be an element of legal and ax- iological pluralism and at the same time a tool (potentially) accommodating pluralism.